Traumatic Memory in Ukrainian Literary Reception: Symptoms of Post-dependence: Tравматична пам’ять в українській літературній рецепції: симптоми постзалежності - Pukhonska, Oksana (Przegląd Wschodnioeuropejski, 2019)
The paper is devoted to analysis of the post-totalitarian memory in literary reception of Ukraine. After the decades of ignoring, this memory became the driving force of social processes and the construct of national identity. The author pays attention to the social trauma of soviet repressions and Second World War, which negatively influenced cultural consciousness of the society. Displaced and forgotten memory is understood as the main reason for lack of progress in the post-Soviet Ukraine. The traumatic experience of the past turned out to be both a lesson and an incentive for large-scale public and conscious transformations, about which modern authors write.